Analyzing digital communication: a comprehensive literature review - Christina Strauss; Michael Dominic Harr; Torsten M. Pieper (Management Review Quarterly, 2024)
Abstract Digital communication has become an essential part of both personal and professional contexts. However, unique characteristics of digital communication—such as lacking non-verbal cues or time asynchrony—clearly distinguish this new form of communication from traditional face-to-face communication. These differences raise questions about the transferability of previous findings on traditional communication to the digital communication context and emphasize the need for specialized research. To support and guide research on the analysis of digital communication, we conducted a systematic literature review encompassing 84 publications on digital communication in leading journals. By doing so, we provide an overview of the current body of research. Thereby, we focus on distinct fields of communication, methods used to collect and analyze digital communication data, as well as common methodological limitations. Building on these insights, we derive a series of comprehensive guidelines from five distinct areas for the collection and analysis of digital communication that can guide future research and organizational practice.
Additional information: M00;O30
Keywords: 330; Digital; Communication; Guidelines; Literature review; Digital transformation